LEARNING DESIGN OPERATION MULTIPLICATION ALGEBRA USING WATER CONTEXT, OIL AND STONE STUDENTS CLASS V - Rahmawati Suandi (Universitas Negeri Makassar, 2018)
The purpose of this study resulted in the learning path of students of algebraic multiplication materials by using water, oil and stone that evolved from informal to formal forms. The method used is a research design consisting of three stages, namely preliminary, design experiment and retrospective analysis. A series of lessons are designed and developed based on conjectures from the learning process and PMRI approach. This research was conducted in SMP N 5 Palembang involving 30 students of class VII. Learning Trajectory (LT) obtained includes three activities that are activities 1. Introduce the objects around that can be used in learning algebraic multiplication such as oil, stone and water, 2 Finding the Concept of Multiplication Algebra and 3. Solving problems related to daily life. The results of the experimental learning show that a series of activities that have been done helps to improve students' understanding of algebraic multiplication learning